The Language of The Novel Rantau 1 Muara by Ahmad Fuadi Studies Stylistics and its Relevance as Teaching Material in High School - Razali Ismail Hadipuro; Mukti Widayati (Universitas Muhammadiyah Ponorogo, 2023)
This article analyses the language style contained in Ahmad Fuadi's Novel Rantau 1 Muara and the relevance of language style to high school learning. In the novel, there are four types of language styles, namely comparative language styles consisting of metaphors, personifications, pleonasm, antitheses, and parables. . The style of the Looping language consists of assonance and metaphor. Linking language style consisting of synecdoche, illusion, euphemisms, and asyndeton. Based on the results of the study, it can be concluded that Ahmad Fuadi's novel Rantau 1 Muara uses a comparative language style, affirmation, and some benefits and lessons can be taken by readers and have language style implications in the world of education, especially as teaching material and language learning in high schools. The research method used to examine the major used in Ahmad Fuadi's novel Rantau Muara is a qualitative descriptive method. The object of this study is the constructive structure and style of language used in Ahmad Fuadi's novel Rantau Muara. This study's data collection techniques used library, listening, and note-taking techniques. The validity of the data in this study uses theoretical triangulation techniques. The data analysis technique in this study uses the semiotic model reading method. Meanwhile, the analysis of stylistic studies in this study was carried out by reading. Re-understanding the data obtained, then grouping the texts in Ahmad Fuadi's novel Rantau Muara per the aspects studied